2006
DOI: 10.2174/092986706777442075
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Efficient Lead Structure Discovery from Natural Products

Abstract: This investigation aims to evaluate strategies for an efficient selection of bioactive compounds from the multitude and biodiversity of the plant kingdom. Statistics prove natural products (NPs) as a source leading most consistently to successful development of new drugs. However, there are several reasons why the interest in finding bioactive NPs has generally declined at several major pharmaceutical companies. Their substantial argument is that the research in this field is time-consuming, highly complex and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 97 publications
0
66
0
1
Order By: Relevance
“…Reverse pharmacology also known as ''target based drug discovery'' became popular after the sequencing of the human genome which allowed for the rapid cloning and synthesis of large quantities of purified proteins. In this context ''Bedside to Bench'' approaches in combinations with systems biology may also be of great interest and the application of a combination of ethno-pharmacological know-how with modern in silico tools may lead to the discovery of new NPs (Rollinger et al 2006;Rollinger 2011). Gene differential expression technologies in mechanistic studies of NP-derived drugs have also shown to be of significant potential (Chen and Jiang 2012).…”
Section: From Clinical Trials On Traditional Medicines To Bioactive Nmentioning
confidence: 99%
“…Reverse pharmacology also known as ''target based drug discovery'' became popular after the sequencing of the human genome which allowed for the rapid cloning and synthesis of large quantities of purified proteins. In this context ''Bedside to Bench'' approaches in combinations with systems biology may also be of great interest and the application of a combination of ethno-pharmacological know-how with modern in silico tools may lead to the discovery of new NPs (Rollinger et al 2006;Rollinger 2011). Gene differential expression technologies in mechanistic studies of NP-derived drugs have also shown to be of significant potential (Chen and Jiang 2012).…”
Section: From Clinical Trials On Traditional Medicines To Bioactive Nmentioning
confidence: 99%
“…Nowadays, the efficient discovery of new lead structures as 5-LO inhibitors from the plant kingdom applies different strategies including ligand-based virtual filtering experiments using pharmacophore models, docking studies and neural networks [202]. For example, by virtual screening of a natural product collection and natural-product-derived combinatorial libraries (430 substances) for potential 5-LO inhibitors grounded on the ªsimilarity principleº, we identified 18 compounds which had mutual pharmacophore features with at least one of 43 known 5-LO inhibitors (that served as query structures) [203].…”
Section: Alkaloidsmentioning
confidence: 99%
“…The large number of natural product-derived antibiotics may be due, in part, to the evolution of secondary metabolites as a defense strategy against the environmental stresses. This feature, coupled with their huge structural diversity and great biodiversity, makes natural products an outstanding and challenging subject to drug discovery and development (Rollinger et al, 2006). It is estimated that infectious diseases are directly responsible for 26% of annual deaths worldwide (Morens et al, 2008).…”
Section: Introductionmentioning
confidence: 99%